The Reenchantment of science: postmodern proposals - Griffin, David Ray (SUNY series in constructive postmodern thought, 1988)
The cosmic creation story / Brian Swimme -- Postmodern science and a postmodern world / David Bohm -- The postmodern challenge to biology / Charles Birch -- The laws of nature as habits / Rupert Sheldrake -- Religious world modeling and postmodern science / Frederick Ferré -- Ecology, science, and religion / John B. Cobb, Jr. -- The postmodern heresy--consciousness as causal / Willis W. Harman -- Parapsychology and postmodern science / Stanley Krippner -- Of minds and molecules / David Ray Griffin